2016
DOI: 10.5152/iao.2016.2004
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implantation in a Patient with Kabuki Syndrome

Abstract: Criteria for cochlear implants are expanding and now include children with disabilities in addition to hearing loss, such as those with Kabuki syndrome (KS). This case report describes language outcomes and changes in the quality of life of a female child with KS after cochlear implantation. The subject had a profound progressive sensorineural hearing loss, cognitive impairments, and other disabilities and communicated using vocalized sounds and the Dutch Sign Language. After cochlear implantation at an age of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Intense acoustic stimulation leads to this reflex, and lesions or traumas in this pathway are reflected as a reduced response to stimulus, suggesting hearing impairment. Hearing loss is one of the neurosensory abnormalities of KS observed over 30% of the patients …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intense acoustic stimulation leads to this reflex, and lesions or traumas in this pathway are reflected as a reduced response to stimulus, suggesting hearing impairment. Hearing loss is one of the neurosensory abnormalities of KS observed over 30% of the patients …”
Section: Discussionmentioning
confidence: 99%
“…Hearing loss is one of the neurosensory abnormalities of KS observed over 30% of the patients. [48][49][50] As for the psychomotor system aspect, surface righting reflex impairment and hindquarter fall was observed in the bapa mutant, which potentially presupposes the presence of hypotonia in these animals. Hypotonia is often noticed from birth in patients with KS, affecting approximately 70% of patients, 48,51 and this clinical feature could be linked to the presence of a KMT2D mutation.…”
Section: Bjornsson Et Almentioning
confidence: 99%
“…Identification of anatomic inner ear abnormalities may have implications for treatment of the hearing loss. For example, one case study demonstrated the efficacy of cochlear implantation in a patient with Kabuki syndrome and semicircular canal malformation (A. Vesseur et al, 2016a). et al, 2018).…”
Section: The Infant's Ultimate Diagnosis Of An Allelic Disorder Cause...mentioning
confidence: 99%